Dispersal Status of Cutaneous Leishmaniasis in Mazandaran Province, 2009-2017 - Leila Ghavibazou; Nasibeh Hosseini-Vasoukolaei; Amir Ahmad Akhavan; Elham Jahanifard; Jamshid Yazdani-Charati; Mahmoud Fazeli-Dinan (Journal of Mazandaran University of Medical Sciences, 2018)
Background and purpose: The leishmaniases are a group of diseases that appear as cutaneous, mucocutaneous, and visceral leishmaniasis, transmitted by different species of sand flies. Cutaneous leishmaniasis (CL) is considered as a major public health problem in Iran. The current study was carried out to determine the spatial and temporal distribution of CL in Mazandaran Province, Iran according to Geographical Information System (GIS). Materials and methods: This retrospective descriptive study was carried out according to demographic and epidemiologic data collected from patients diagnosed with CL during 2009-2017 recorded in Health deputy of Mazandaran University of Medical Sciences. The spatial and temporal distribution of CL in different cities of Mazandaran Province was mapped using ArcGIS 10.4 software. Results: The number of patients with CL was 378 during the years studied. The highest and lowest numbers of CL patients were seen in Sari and Abbas Abad, respectively (n=71, n=2, respectively). Most of the cases (n= 182) were reported in east of Mazandaran and the least number of cases (n= 73) were observed in the west of province. The incidence rate in the west of the province was lower than that of the center and east of the province. Conclusion: Distribution of CL in Iran, agricultural activities, livestock breeding, and migratory status in Mazandaran Province call for appropriate planning to control this disease.